AICCRA Continental Level Stakeholder Consultation Report - Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report presents the findings of continental level stakeholder consultations conducted by the Policy theme of AICCRA during the month of September 2023. We undertook these consultations to gather inputs from stakeholders and feed them into the design process of the AICCRA Additional Financing (AF). Conversations with stakeholders focused on understanding the challenges faced, the opportunities presented and the priorities for AICCRA’s AF from various stakeholder perspectives. The main challenges noted were an overall need for longer term funding from African development partners, the lack of political stability in West Africa and issues related to cascading transboundary climate risks. Various opportunities that were mentioned included providing embedded support to African institutes, engaging policy makers from initial stages of project design to get buy in and support during implementation and increasing collaboration with existing partners to work in different countries where they have presence. Some of the major priorities highlighted included focusing more on youth groups, improving access to finance and giving more emphasis to medium and late-stage agri-businesses and shifting from government-led to farmer-led initiatives.